2002
DOI: 10.1017/s0958344002000319
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and task performance in a task-based web-based tandem project

Abstract: The objective of this paper is to describe a task-based project in tandem via e-mail, and to discuss the effects of motivation on task performance. In this project, a group of Irish students and a group of Spanish students are asked to carry out a series of tasks in collaboration with their tandem partners via e-mail by means of a web page especially designed for the project. Half the message is meant to be written in the student’s native language and half in the target language, and students are also enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 11 publications
2
21
0
2
Order By: Relevance
“…Positive effects of the application of computer technology have been revealed in many studies and its supportive outcomes in classrooms have been reported (Appel & Gilabert, 2002;Chang, 2005;García & Arias, 2000;Jerrell & Freiermuth, 2005).…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…Positive effects of the application of computer technology have been revealed in many studies and its supportive outcomes in classrooms have been reported (Appel & Gilabert, 2002;Chang, 2005;García & Arias, 2000;Jerrell & Freiermuth, 2005).…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…To obtain a reliable corpus of analysis based on interaction between participants is considered one of the problem areas in email tandem (Appel & Mullen, 2000;Appel & Gilabert, 2002;Appel & Mullen, 2002). With the aim of avoiding previously reported issues (copies of emails not sent to the coordinator, duplicates, disorganized or manipulated copies of emails, etc.)…”
Section: Description and Methodologymentioning
confidence: 99%
“…Since then, calls can be made over the Internet across the world at no marginal cost, through free software such as Skype or GoogleTalk, even replacing landline technology (Graddol, 2006). Research has shown that online language exchange projects of this nature can contribute to the development of learner autonomy (O'Rourke, 2005;Schwienhorst, 2000;Newby et al 2007), linguistic accuracy (Kinginger and Belz, 2005;O'Rourke, 2005;Ware and O'Dowd, 2008), intercultural awareness (Müller-Hartmann, 2000;O'Dowd and Ritter, 2006;Ware, 2005), intercultural skills (Belz and Müller-Hartmann, 2003;Thorne, 2010), electronic literacies (Hauck, 2010), and task development (Appel and Gilabert, 2002;Furstenberg, Levet, English, and Maillet, 2001;Müller-Hartmann, 2000;Waire, 2008, 2009).…”
Section: Using Ict To Contact the Target Culturementioning
confidence: 99%